Pengaruh Leverage dan Ukuran Perusaaan Pada Nilai Perusahaan - Anugerah, Kevin Hestia Gigih; Suryanawa, I Ketut (E-Jurnal Akuntansi; Vol 26 No 3 (2019), 2019)
To maximize the welfare of stakeholders, can be achieved by maximizing the value of the company. But sometimes companies fail to increase that, because of less conscientious in applying factors influencing the value of enterprise. The purpose of this study was to determine the effect of leverage and the size of the company in the pharmaceutical sector enterprise value on the Stock Exchange. The population in this study is pharmaceutical sector companies listed on the Stock Exchange in the period 2013-2016 which amounted to 10 companies. Sampling technique used was purposive sampling, the samples obtained are 8 companies. Data collection methods used is non-participant observation. Sources of data is secondary data obtained from www.idx.co.id . The data analysis technique used is multiple linear regression. Based on the analysis shows leverage significant negative effect, and the size of the company and significant positive effect on the value of the company. Keywords: Enterprise value, leverage,company size